If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + -2 + -2 + 15 = 1 + 3a Reorder the terms: -2 + -2 + 15 + a = 1 + 3a Combine like terms: -2 + -2 = -4 -4 + 15 + a = 1 + 3a Combine like terms: -4 + 15 = 11 11 + a = 1 + 3a Solving 11 + a = 1 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. 11 + a + -3a = 1 + 3a + -3a Combine like terms: a + -3a = -2a 11 + -2a = 1 + 3a + -3a Combine like terms: 3a + -3a = 0 11 + -2a = 1 + 0 11 + -2a = 1 Add '-11' to each side of the equation. 11 + -11 + -2a = 1 + -11 Combine like terms: 11 + -11 = 0 0 + -2a = 1 + -11 -2a = 1 + -11 Combine like terms: 1 + -11 = -10 -2a = -10 Divide each side by '-2'. a = 5 Simplifying a = 5
| 49h+20=314 | | -2x-6=-2-4 | | 4p+2+2p+1=8 | | -5x+9=17-x | | 6y=8x-10 | | 10t^2=12t+23 | | C+c=73 | | -3(-4-6y)+7(y+5)= | | 75+2x=0-15 | | 4+x=200 | | 4x^2+4x+32=0 | | 4x+1+3x=-3 | | 2x^2+3+3=-7x | | Y=2x+(-8) | | -15x+9=17-x | | 4X-8=3(2X-4) | | 75+2x=15 | | X+2=2overy-1 | | +t/12=-3 | | -6b+28=9b-2 | | 3x-9=4x-24 | | 3(4x+1)=3+12x-3 | | 36+2y-15=12y-9-5y | | 8-4+2R-4R+8R= | | 2L+2W=W+84 | | 8-r=3r-14 | | x-1b=72 | | .666h-9=6-.666h | | 8x+6y-10=0 | | 24b+4=52 | | (x-3)(x-4)-(x+4)=0 | | 2n^3-24n^2-23048n=0 |